Kendig and Chernick's disorders of the respiratory tract in children - 4 0 16; (Robert W.) 1911- Kendig, Edwin L.,;Wilmott, R. W.; 5 (Philadelphia, PA : Elsevier/Saunders, 2012)
Kendig, Chernick's Disorders of the Respiratory Tract in Children is the definitive medical reference book to help you confront critical challenges using the latest knowledge and techniques. You'll get the state-of-the-art answers you need to offer the best care to young patients.--Publisher's website.
General Basic Considerations. Molecular Determinants of Lung Morphogenesis ; Basic Genetic and Epigenetics of Childhood Lung Disease ; Gene by Environment Interaction in Respiratory Diseases ; The Surfactant System ; The Structural and Physiologic Basis of Respiratory Disease ; Biology and Assessment of Airway Inflammation ; Lung Defenses: Intrinsic, Innate, and Adaptive. -- General Clinical Considerations. The History and Physical Examination ; Bronchoscopy and Bronchoalveolar Lavage in Pediatric Patients ; Diagnostic Imaging of the Respiratory Tract ; Pulmonary Function Tests in Infants and Preschool Children ; Pulmonary Function Testing in Children ; Exercise and Lung Function in Child Health and Disease ; Integrating Patient-Reported Outcomes into Research and Clinical Practice ; Children Dependent on Respiratory Technology ; Transition from Pediatric to Adult Care ; Long-Term Consequences of Childhood Respiratory Disease ; Drug Administration by Inhalation in Children ; Physical Therapies in Pediatric Respiratory Disease ; Modern Molecular Therapies for Respiratory Disease. -- Respiratory Disorders in the Newborn ; Congenital Lung Disease ; Respiratory Disorders in the Newborn ; Bronchopulmonary Dysplasia. -- Infections of the Respiratory Tract. Microbiologic Diagnosis of Respiratory Illness: Practical Applications ; Acute Infections That Produce Upper Airway Obstruction ; Bronchitis ; Bronchiolitis ; Viral Pneumonia ; Community-Acquired Bacterial Pneumonia ; Bronchiectasis and Chronic Suppurative Lung Disease. -- Infections of the Respiratory Tract Due to Specific Organisms. Influenza ; Atypical Pneumonias in Children ; Tuberculosis and Nontuberculosis Mycobacterial Disease ; The Mycoses ; Pertussis and Other Bordetella Infections of the Respiratory Tract ; Toxocariasis, Hydatid Disease of the Lung, Strongyloidiasis, and Pulmonary Paragonimiasis. -- Noninfectious Disorders of the Respiratory Tract ; Atelectasis ; Pulmonary Edema ; Acute Respiratory Distress Syndrome ; Lung Injury from Hydrocarbon Aspiration and Smoke Inhalation ; Drowning ; Tumors of the Chest ; Chest Wall Function and Respiratory Muscle Disorders. -- Asthma. The Epidemiology of Asthma ; The Immunopathogenesis of Asthma ; Asthma in the Preschool-Age Child ; Wheezing in Older Children: Asthma ; Severe Asthma ; The Influence of Upper Airway Disease on the Lower Airway. -- Cystic Fibrosis. Genetics and Pathophysiology of Cystic Fibrosis ; Diagnosis and Presentation of Cystic Fibrosis ; Pulmonary Disease in Cystic Fibrosis ; Nonpulmonary Manifestations of Cystic Fibrosis. -- chILD. New Concepts in Children's Interstitial Lung Disease and Diffuse Lung Disease ; Childhood Interstitial Lung Disease Disorders More Prevalent in Infancy ; Lung Diseases Associated with Disruption of Pulmonary Surfactant Homeostasis ; Pulmonary Involvement in the Systemic Inflammatory Diseases of Childhood ; Diffuse Alveolar Hemorrhage in Children ; Environmental Exposures in the Normal Host ; Rare Childhood Lung Disorders. -- Disorders of the Immunocompromised Child ; Primary Immunodeficiency: Chronic Granulomatous Disease and Common Variable Immunodeficiency Disorders ; Pulmonary Disease in the Pediatric Patient with Acquired Immunodeficiency States ; Respiratory Disorders in Pediatric HIV Infection ; Pediatric Lung Transplantation. -- Aerodigestive Disease ; The Aerodigestive Model ; Aspiration ; Feeding, Swallowing, and Voice Disorders ; Gastroesophageal Reflux Disease and Eosinophilic Esophagitis in Children with Complex Airway Disease ; Laryngeal and Tracheal Airway Disorders. -- Other Diseases with a Prominent Respiratory Component. Air and Liquid in the Pleural Space ; Primary Ciliary Dyskinesia ; Childhood Pulmonary Arterial Hypertension ; The Lung in Sickle Cell Disease ; Lung Injury Caused by Pharmacologic Agents ; Disorders of the Respiratory Tract Caused by Trauma ; Sudden Infant Death Syndrome and Apparent Life-Threatening Events ; Disorders of Breathing During Sleep.
Rev. ed. of: Kendig's disorders of the respiratory tract in children. 7th ed. c2006.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Pediatric respiratory diseases.;Respiratory Tract Diseases.;Child.;Infant. -- 20; 20; 2